2005
DOI: 10.1897/04-474r.1
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals, stable isotope ratios, and trophic relations in seabirds from the North Pacific Ocean

Abstract: Trace elements including mercury, cadmium, selenium, and stable nitrogen isotope ratios (sigma15N) were measured in tissues of Pacific seabirds. Two species of albatross (Diomedea immutabilis, Diomedea nigripes), four species of shearwaters (Puffinus bulleri, Puffinus carneipes, Puffinus griseus, Puffinus tenuirostris), northern fulmar (Fulmarus glacialis), and horned puffin (Fratercula corniculata) were collected opportunistically by an experimental fishery in the North Pacific Ocean. Two species each of petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
(81 reference statements)
7
10
2
Order By: Relevance
“…The Cd concentrations in livers of Arctic seabirds reported in the present study were at the higher end of the range of Cd levels reported for other seabird species from both the Canadian Pacific coast [7,30] and Atlantic coast [6], with the exception of the storm‐petrels from the Pacific coast, which had considerably higher concentrations (Leach's storm‐petrel, 82‐100 μg/g dry wt, fork‐tailed petrel [ Oceanodroma furcata ], 142 μg/g dry wt) than all other species on both the eastern and western coasts. The hepatic Cd concentration for northern fulmars from the present study was approximately fourfold higher than that found for northern fulmars from the northern Pacific Ocean [30].…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The Cd concentrations in livers of Arctic seabirds reported in the present study were at the higher end of the range of Cd levels reported for other seabird species from both the Canadian Pacific coast [7,30] and Atlantic coast [6], with the exception of the storm‐petrels from the Pacific coast, which had considerably higher concentrations (Leach's storm‐petrel, 82‐100 μg/g dry wt, fork‐tailed petrel [ Oceanodroma furcata ], 142 μg/g dry wt) than all other species on both the eastern and western coasts. The hepatic Cd concentration for northern fulmars from the present study was approximately fourfold higher than that found for northern fulmars from the northern Pacific Ocean [30].…”
Section: Discussioncontrasting
confidence: 44%
“…Lead. Concentrations of hepatic Pb were either not detectable or very low in all seabird species from all of Canada's coasts [6,7,22,30] (present study).…”
Section: Discussionmentioning
confidence: 83%
“…Northern fulmars and storm petrels became the main food resource, the use of other bird species, marine invertebrates and otarid products having significantly decreased [7]. The Northern fulmar ( Fulmarus glacialis ) breeds on Siberian and Alaskan islands and winters widely throughout the Pacific, feeding mainly on invertebrates and some fish [39] whereas the two storm petrels species ( Oceanodroma furcata and O. leucorhoa ) are pelagic plankton eaters [40]. Due to their relatively lower position within the food chain it is very likely that these bird species are generally less contaminated with Hg or other pollutants than seals.…”
Section: Discussionmentioning
confidence: 99%
“…If king eiders and whitewinged scoters are similar to common eiders in this regard, it is plausible that Hg could exacerbate the adverse effects of other environmental stressors. Total Hg levels in eiders, scoters, and other sea ducks are relatively low, however, especially compared to pelagic marine birds and fish-eating birds [5][6][7]43]. Moreover, marine birds, presumably including sea ducks, generally are well-adapted for coping with exposure to elevated Hg levels [44].…”
Section: Discussionmentioning
confidence: 99%